Treatment of Teeth with Apical Root Resorption Using MTA - Selin İsaoğlu Bulut; Emre Bodrumlu (JOURNAL OF BIOTECHNOLOGY AND STRATEGIC HEALTH RESEARCH, 2026)
ABSTRACTObjective: Apical stenosis may be impaired due to pulpal pathologies, iatrogenically, etc. Apical inflammatory root resorption usually occurs due to periapical pathology without any clinical symptoms. The aim of this case series is to utilize calcium silicate based materials to provide hermetic occlusion in the treatment of teeth with compromised apical integrity. Case Report: Case 1: A 21-year-old woman with no systemic disease. Tooth number 11 had swelling and fistula tract extending to the buccal mucosa. Clinical examination revealed inadequate and incomplete root canal treatment and extensive lesion in the apical region. The old root canal treatment was removed. Apical narrowing was found to be impaired. After dressing with Ca(OH)2, MTA (mineral trioxide aggregate) was placed in the apical region. Root canal treatment was completed with the warm vertical condensation technique in the middle and coronal region of the root. Six months later, the patient was called for a follow-up visit and it was observed that all objective complaints had resolved and the periapical lesion had disappeared in the radiographs.Case 2: A 43-year-old male patient with no systemic disease. Radiographic images obtained from the patient revealed dentigerous cysts affecting teeth number 38 and 37. External root resorption was detected in the distal canal of tooth number 37. The entire distal canal of tooth number 37 was filled with MTA and the mesial canals were filled with gutta percha. Tooth number 38 was extracted and the dentigerous cyst was enucleated. The patient was called for follow-up three and six months later and it was determined that all objective complaints had resolved and the borders of the periapical lesions had healed in the radiographs. Conclusion: In cases of external root resorption with impaired apical stenosis, conservative endodontic treatment with effective irrigation, Ca(OH)2 medicaid and MTA in combination with an apical plug is one of the successful treatment options.Key words: Periapical pathology, external root resorption, mineral trioxide aggregate